The Knowledge Bottleneck: Analyzing Barriers to Effective Knowledge Management System (KMS) Use in Public Institutions - Irfan Ramdani; Khaerudin Khaerudin; Iva Sarifah; Cep Ubad Abdullah (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
In the era of digital transformation, Knowledge Management Systems (KMS) play a pivotal role in improving transparency, efficiency, and organizational learning across public institutions. Despite their potential, many governments—particularly in developing contexts—continue to experience uneven implementation outcomes. This study aims to identify the primary barriers and enablers influencing the successful adoption of KMS in public sector organizations. Employing a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol, the research systematically analyzed 22 empirical studies published between 2006 and 2024 retrieved from Scopus and Web of Science databases. The synthesis reveals that technological, organizational, and human factors jointly shape KMS success. Common barriers include inadequate ICT infrastructure, bureaucratic rigidity, resistance to change, and low digital literacy. Conversely, leadership commitment, supportive culture, technological integration, and policy alignment emerge as key enablers. Interpreted through the Technology–Organization–Environment (TOE) framework, the Knowledge-Based View (KBV), and Socio-Technical Systems (STS) theory, the findings underscore that technological sophistication alone does not ensure effectiveness—strategic leadership and cultural transformation are equally critical. The study contributes a holistic understanding of KMS implementation dynamics in the public sector and offers evidence-based insights for policymakers to strengthen knowledge governance and institutional innovation.